Algorithms and agency in hospitals: Empirical insights on the impact of digital transformation on clinical work - Pauline Kuss; Christian Meske; Martin Gersch; Felix Balzer; Daniel Fürstenau; Alica Thissen; Marc Dewey; Florian Michallek; Josch Füllhase (Hans-Böckler-Stiftung, 2024)
This whitepaper based on the "Algorithms and Agency in Hospitals" project delves into the effects of digital transformation on the work of healthcare professionals and seeks methods to represent their interests throughout this process. Two case studies were carried out in collaboration with Charité Berlin, focusing on the impact of documentation software and algorithm-based decision support tools on clinical workflows, diagnostics, patient care, and the individual's sense of agency. The results underscore the importance of sufficient resources and a user-centered approach to technology design in supporting clinicians' work. The whitepaper concludes with recommendations for clinical managers, employee groups and their representatives, as well as policymakers.
Keywords: 330; artificial intelligence; digitalization; healthcare; decision support; radiology